Decoupling state computation and state dissemination for scalable virtual environments using spatial publish/subscribe - Smit, Petrus Jurgens (Stellenbosch : Stellenbosch University, 2025)
Smit, P. J. 2025. Decoupling State Computation and State Dissemination for Scalable Virtual Environments Using Spatial Publish/Subscribe. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/abed4cb9-6163-45d3-875b-b440ab884562